Asistensi Mengajar (AM) Program in Merdeka Belajar Kampus Merdeka (MBKM) as A Pedagogical Mastery Accelerator for Vocational High School Teacher Candidates - Muhammad Idris Effendi; Yoto Yoto; Widiyanti Widiyanti (Jurnal Pendidikan Sains, 2024)
This research delves into the issue of inadequate pedagogical proficiency among vocational high school (SMK) teacher candidates, primarily stemming from the constrained timeframe of educational internships, typically spanning a mere two months. As an option, this study suggests the implementation of an Asistensi Mengajar (AM) initiative within the framework of the Merdeka Belajar Kampus Merdeka Program (MBKM), extending over a semester’s duration. Employing a literature review methodology, the research highlights that the brevity of conventional two-month internships poses a significant impediment to the development of pedagogical acumen among SMK teacher candidates. The proposed option entails an AM program under MBKM, engaging students in bolstering literacy, numeracy, technological adaptability, and school administration skills. The emphasis is laid on the pivotal role of pedagogical competence in ensuring efficacious and dynamic learning processes. A comprehensive grasp of the constituents of pedagogical competence, encompassing sub-competencies and corresponding indicators, is deemed indispensable. Prior studies have evidenced a positive correlation between heightened pedagogical competence and learning efficacy. It is recommended that AM-MBKM programs be extended to students, affording them opportunities to partake in collaborative learning endeavors under the tutelage of teachers and mentoring lecturers within formal educational settings.DOI: 10.17977/jps.v12i22024p057